PENINGKATAN PENGETAHUAN DAN SKREENING KELAINAN REFRAKSI DINI PADA ANAK USIA SEKOLAH DI NATAR LAMPUNG SELATAN [INCREASING THE KNOWLEDGE AND EARLY SCREENING OF REFRACTIVE ABNORMALITIES IN SCHOOL AGE CHILDREN AT NATAR LAMPUNG SELATAN] - Rani Himayani; Soraya Rahmanisa (Jurnal Sinergitas PKM & CSR, 2018)
Background: Early detection of refractive abnormalities at late school age causes a decrease visual in children as a barrier in learning activities and carrying out daily activities, which can affect children's learning achievement. High refractive abnormalities that are not well corrected can cause lazy eyes in children. Objective: Increased knowledge and awareness of both children, parents and teachers regarding the importance of periodic control in children so that refractive abnormalities can be early detected at school age. Methods: screening of refractive abnormalities in children and eye examination by experts. Results: There were 56 children of Elementary School in South Lampung who were selected to attend counseling and eye screening. Based on data from pre-test observations, it was found that 61% of participants did not understand the knowledge of refractive abnormalities and 39% knew sufficient knowledge about refractive abnormalities. After counseling activities, the value of the observation results increases. Most participants understand about the knowledge of refractive disorders. The results of the screening for refraction abnormalities from 56 elementary school children found that 12 children experienced refractive error consisting of 3 boys and 9 girls. Children who detected refractive abnormalities were examined further and given treatment of prescription glasses. Conclusion: This program can help detect early if there are refractive abnormalities in school-age children so they can immediately get the treatment.